Lipid-Based Nanostructures for Food Encapsulation Purposes Volume 2 in the Nanoencapsulation in the Food Industry series - Jafari, Seid Mahdi; Jafari, Seid Mahdi (Academic Press, 2019)
Lipid-Based Nanostructures for Food Encapsulation Purposes, Volume Two in the Nanoencapsulation in the Food Industry series, reviews recent studies on the formulation and evaluation of different categories of lipid-based nano-carriers and discusses how lipid nanoencapsulation is a feasible technology for the food industry. This book covers nano-emulsions, nano-liposomes, nanostructured lipid carriers and surfactant nanoparticles. Authored by a team of global experts in the fields of nano and microencapsulation of food, nutraceutical and pharmaceutical ingredients, this title is of great value to those engaged in the various fields of nanoencapsulation. - Provides recent studies on the formulation and evaluation of different categories of lipid-based nanocarriers - Discusses how technology of lipid nanoencapsulation can be used in industries - Summarizes the practical application of nanostructures from lipid formulations, such as nanoemulsions, nanoliposomes and nanostructured lipid carriers